Recent Progress in antibacterial hydrogel coatings for targeting biofilm to prevent orthopedic implant-associated infections - Wang, Mengxuan; Zheng, Yawen; Yin, Chuqiang; Dai, Shiyou; Fan, Xiao; Jiang, Ying; Liu, Xuequan; Fang, Junqiang; Yi, Bingcheng; Zhou, Qihui; Wang, Ting (Frontiers in Microbiology, 2023)
The application of orthopedic implants for bone tissue reconstruction and functional restoration is crucial for patients with severe bone fractures and defects. However, the abiotic nature of orthopedic implants allows bacterial adhesion and colonization, leading to the formation of bacterial biofilms on the implant surface. This can result in implant failure and severe complications such as osteomyelitis and septic arthritis. The emergence of antibiotic-resistant bacteria and the limited efficacy of drugs against biofilms have increased the risk of orthopedic implant-associated infections (OIAI), necessitating the development of alternative therapeutics. In this regard, antibacterial hydrogels based on bacteria repelling, contact killing, drug delivery, or external assistance strategies have been extensively investigated for coating orthopedic implants through surface modification, offering a promising approach to target biofilm formation and prevent OIAI. This review provides an overview of recent advancements in the application of antibacterial hydrogel coatings for preventing OIAI by targeting biofilm formation. The topics covered include: (1) the mechanisms underlying OIAI occurrence and the role of biofilms in exacerbating OIAI development; (2) current strategies to impart anti-biofilm properties to hydrogel coatings and the mechanisms involved in treating OIAI. This article aims to summarize the progress in antibacterial hydrogel coatings for OIAI prevention, providing valuable insights and facilitating the development of prognostic markers for the design of effective antibacterial orthopedic implants.